2015
DOI: 10.1007/s00382-015-2843-3
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of air–sea heat fluxes from ocean and coupled reanalyses

Abstract: and assimilation increments is concentrated in the upper 100 m. Implied steady meridional heat transports also improve by including assimilation sources, except near the equator. The ensemble spread in surface heat fluxes is dominated by turbulent fluxes (>40 W m −2 over the western boundary currents). The mean seasonal cycle is highly consistent, with variability between products mostly <10 W m This paper is a contribution to the special issue on ocean estimation from an ensemble of global ocean reanalyses, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 66 publications
2
86
0
Order By: Relevance
“…Differences in MDT and both hydrography and altimeter assimilation methods are particularly important in the Southern Ocean, and may explain the large spread and positive/negative dipoles exhibited in that region. Differences in the North Atlantic sector are likely associated with differing representation of the Atlantic meridional overturning circulation and the associated heat transport (Pohlmann et al 2013;Valdivieso et al 2015). While model resolution affects the simulation of the AMOC, studies have shown that the mean value can be reasonably well represented in ¼ degree models (Roberts et al 2013), although the associated heat transports are too weak (Haines et al 2013).…”
Section: Time-mean and Amplitude Of The Seasonal Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Differences in MDT and both hydrography and altimeter assimilation methods are particularly important in the Southern Ocean, and may explain the large spread and positive/negative dipoles exhibited in that region. Differences in the North Atlantic sector are likely associated with differing representation of the Atlantic meridional overturning circulation and the associated heat transport (Pohlmann et al 2013;Valdivieso et al 2015). While model resolution affects the simulation of the AMOC, studies have shown that the mean value can be reasonably well represented in ¼ degree models (Roberts et al 2013), although the associated heat transports are too weak (Haines et al 2013).…”
Section: Time-mean and Amplitude Of The Seasonal Cyclementioning
confidence: 99%
“…Disentangling the roles of differing ocean vertical mixing, (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) ocean circulation and surface forcings in determining these biases is a challenging problem and requires further and detailed analysis. Errors in both momentum and heat fluxes have a role here (Lee et al 2013;Valdivieso et al 2015) and consideration of mixed layer depths may also offer additional insights . The representation of vertical mixing in ocean models remains an area that requires particular attention due to the different mixing schemes, related parameters and the often poorly quantified effects of numerical mixing (e.g.…”
Section: Time-mean and Amplitude Of The Seasonal Cyclementioning
confidence: 99%
“…Improvement in representing MLDs in this region is needed in the future. To do so, intercomparisons for sea ice (e.g., Smith et al 2014) and surface flux (e.g., Valdivieso et al 2014) might indicate important clues in association with deep convection following the sea ice formation by strong cooling. Further observations in the Southern Ocean, particularly for the sea ice region, are also important, indicated by large differences between MILA-GPV and EN3v2a/ ARMOR3D with their signs changing on small scales.…”
Section: Seasonal and Interannual Variations Of Mldsmentioning
confidence: 99%
“…Valdivieso et al [2015] showed that most reanalysis products feature a bias during the period 1993-2009 in the global-mean net surface flux in the order of 1-2 W/m 2 which is larger than the energy gain derived from estimates of the top of atmosphere (TOA) imbalance of about 0.50 (±0.43) W/m 2 [Loeb et al, 2012]. For comparison, the current generation of climate models of the Coupled Model Intercomparison Project Phase 5 (CMIP5) exhibits an uncertainty in the net surface and TOA fluxes in the order of 10 W/m 2 and 5 W/m 2 , respectively [Wild et al, 2015].…”
Section: Introductionmentioning
confidence: 99%